The Effectivity of Revitalization of Sarinah Building with The New Functions as De Braga by Artotel Hotel - Husna Izzati; Andiyan Andiyan; Okki Nurrisman (Jurnal Arsitektur, 2022)
Braga street known as the old town historical area with colonial building style in Bandung. Braga was an abandon area with poor environment and historical degradation a cause for concern. Many buildings unused and most of this change its functions not as expected that increase the negative perception for Braga area. The effort have been made by the Government and concerned community organizations to restore the existence of the Braga area, accompaned with the legal of cultural heritage area. The Braga area began to be revitalized, in colaborate with many participant including the private sector. One of the revitalized is Sarinah Braga Building. The building was previously a bustling fashion store in the 1970s until finally closed in 1990, was abandoned for more than 10 (ten) years, and has been converted into a boutique hotel with an Art Deco concept. Hotel de Braga consisting of 2 (two) masses, the podium mass which is the ground floor to the 3rd floor, and the tower area 4th to 14th floor. As an adaptation of the regulations, the front building is maintained, with the 'sarinah' sign still being left attached to the wall. Using the mixed methods research, this research performed by analyzing phenomena, conducting observations, interviews, and documentation. From the results of the study, it has found that the physical aspect of the revitalization of the Sarinah building with the new function of Hotel de Braga has met the requirements and achieved a satisfactory level of success. In social, economic, and institutional aspects, the results are still things that need to be improved in terms of empowering the surrounding community, green planning, and the regulation that related of both in the Braga area.